2005
DOI: 10.1128/mcb.25.2.789-796.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prss16 Is Not Required for T-Cell Development

Abstract: PRSS16 is a serine protease expressed exclusively in cortical thymic epithelial cells (cTEC) of the thymus, suggesting that it plays a role in the processing of peptide antigens during the positive selection of T cells. Moreover, the human PRSS16 gene is encoded in a region near the class I major histocompatibility complex (MHC) that has been linked to type 1 diabetes mellitus susceptibility. The mouse orthologue Prss16 is conserved in genetic structure, sequence, and pattern of expression. To study the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…In agreement with previous reports (10,11), Tssp° NOD mice showed normal T cell development and no global defect in positive or negative T cell selection in the thymus (Supplemental Figure 2). Furthermore, the Vβ-segment usage by mature peripheral CD4 and CD8 was similar in Tssp° and WT control mice (Supplemental Figure 3).…”
Section: Tssp° Nod Mice Are Resistant To Insulitis and Diabetessupporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with previous reports (10,11), Tssp° NOD mice showed normal T cell development and no global defect in positive or negative T cell selection in the thymus (Supplemental Figure 2). Furthermore, the Vβ-segment usage by mature peripheral CD4 and CD8 was similar in Tssp° and WT control mice (Supplemental Figure 3).…”
Section: Tssp° Nod Mice Are Resistant To Insulitis and Diabetessupporting
confidence: 81%
“…Mice were immunized with the corresponding Ag in CFA, and their recall response was analyzed in vitro. Quite unexpectedly in light of the foremost role of insulin in diabetes development (31,32), we found that the frequency of IL-2-producing CD4 T cells specific for Ins [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and Ins [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] was comparable in Tssp° and WT NOD mice ( Figure 6). Likewise WT and Tssp° NOD mice responded similarly to the GAD 206-220 peptide and the known IGRP immunodominant epitopes ( Figure 6).…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…The overexpressed genes included several known to be involved in protein synthesis (Eef2, eEF-Tu and Mrpl38), Notch signaling (Dtx1) and Ccl8. Several classes of genes were commonly underexpressed in the pre-T LBL samples, including apoptotic pathway genes (Cox8b and Cidea), 16 genes involved in T-cell differentiation (Prss16, Ccl25, CD83, Spatial, Fkbp6 and Tcrd), [17][18][19][20] a group of fatty acid-binding proteins (Fabp3, Fabp4 and Fabp9), 21 and Bop1 22 and Rb1cc1, 23 two genes whose overexpression is linked to decreased cell proliferation. The Fabp proteins are typically expressed in adipocytes, 21 and their underexpression in pre-T LBL relative to normal thymus may reflect a decreased proportion of adipocytes in the pre-T LBL tumor samples compared to normal thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, development of autoreactive diabetogenic T cells has been suggested to result from inordinate positive selection [11,12]. The function of PRSS16 is still largely unknown, but murine studies of Prss16-deficient mice revealed that Prss16 is not required for quantitatively normal T-cell development or normal surface expression of MHC class II molecules on thymic cortical epithelial cells [13]. However, in human beings, PRSS16 and its splice variants have been shown to be differentially expressed in thymus from myasthenia gravis patients with thymoma compared with myasthenia gravis patients with thymic hyperplasia, suggesting a role in the thymus pathology [14].…”
Section: Introductionmentioning
confidence: 98%